Efektivitas Model Pembelajaran Problem Solving Terhadap Literasi Numerasi Peserta Didik Kelas V SD Negeri 232 Palembang - Linda, Tria Rosa; Puspita, Yenny; Selegi, Susanti Faipri (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The aim of this research is to determine the effectiveness of the problem-solving learning model on the numeracy literacy of class V students at SD Negeri 232 Palembang. This type of research uses quantitative methods with a control group design. Meanwhile, the subjects of this research were class V students at SD Negeri 232 Palembang, where class V.A was the control class and class V.B was the experimental class, each with a total of 32 students, the data collection method used tests and documentation, the test instrument was in the form of essay questions totaling 8 questions.to measure student learning outcomes, data analysis techniques use the t test. The results of the t test calculation found a significance value of 0.017 < α value (0.05), thus Ho was rejected and Ha was accepted. Based on the research results, it can be concluded that the problem-solving learning model is effective on mathematics learning outcomes at SD Negeri 232 Palembang.